Updating of the Problems of Concentre of Ukrainian Studies «Ukraine – Ethnos» under the Conditions of Content Updating of National Education - Maftyn, Larysa (Pedagogical Discourse, 2016)
The article deals with problems of Ukrainian studies concentre «Ukraine – ethnos»; outlined the main innovative approaches to learning concentre appointed in elementary school. The attention that the new stage of development of education in Ukraine is characterized by the departure of authoritarian unification and standardization of educational process, rethinking values, intensive search for a new theory and practice of teaching and education. Many scientists believe that the basis for the transformation of the modern education system in Ukraine, updating the content of education should rest ukrainian studies methodology of training and education, the idea of national and cultural identity, as ukrainian study opens up limitless possibilities to carry out practical steps to implement its major objectives like research , culture and education and in educational areas, including creating effective conditions for the successful development and application of pedagogical innovations: new teaching methods, new ways of employment, innovation in the organization of the curriculum (integration, interdisciplinary program), playing techniques (quizzes, debates ), problem teaching, research organization obtaining new knowledge for students and others. It is stipulated that one of the key problems is the problem of Ukrainian origin, formation and development of the Ukrainian nation. Objective coverage of this issue - the urgent issue of our time - until recently in training programs, textbooks prevailing ideological stereotypes. In soviet times, Ukrainian early history was distorted in favor of the north-eastern neighbor, Ukrainian proclaimed «younger brother» of Russians, and all the gains of the Ukrainian people, especially in the field of culture, interpreted as something accidental, «transitional state of Russian culture». This worked to a certain ideology, formed certain stereotypes, was aimed at belittling the importance of ukrainian history. Therefore, the content and means of education in the new historical conditions are free from political bias, become the new leader of Ukrainian patriotic man who is conscious creator of his country. It is concluded that the Ukrainian study methodology provides structured educational work on the basis of Ukrainian values, the choice of methods, principles and means of education that best promote the formation of ethnic conscious individual - a citizen of Ukraine. A proper understanding of the problems of Ukrainian ethnogenesis allows a deeper understanding of the objective laws of modern globalization, they define the role and place of Ukraine and Ukrainian, enables to solve the tasks that are relevant to independent Ukraine and relate to the ethnic national consciousness, patriotism state, national dignity and self-respect. Key words: pedagogical innovation, Ukrainian studies, ethnicity, descent, sphere of education.